Використання BLENDER, UNITY, THREE.JS для анімації в мультимедіа - Біла, Д. С.; Вовк, О. В. (ХНУРЕ, 2025)
This study examines the use of Blender, Unity, and Three.js in 3D animation for multimedia projects. It analyzes the core functionalities of each tool: Blender for modeling, animation, and rendering, Unity for interactive applications and cross-platform development, and Three.js for real-time 3D visualization in web browsers. The research highlights their integration in multimedia workflows, focusing on strengths, limitations, and compatibility to enhance the creation of high-quality animated content. Special attention is given to the advantages of combining these technologies to achieve more efficient production processes.
Keywords: мультимедіа; аніміція